2008
DOI: 10.1152/japplphysiol.00869.2007
|View full text |Cite
|
Sign up to set email alerts
|

The influence of physical activity on lean mass accrual during adolescence: a longitudinal analysis

Abstract: Baxter-Jones AD, Eisenmann JC, Mirwald RL, Faulkner RA, Bailey DA. The influence of physical activity on lean mass accrual during adolescence: a longitudinal analysis. J Appl Physiol 105: 734-741, 2008. First published May 8, 2008 doi:10.1152/japplphysiol.00869.2007.-During childhood, physical activity is likely the most important modifiable factor for the development of lean mass. However, the effects of normal growth and maturation must be controlled. To distinguish effects of physical activity from normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
72
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 51 publications
8
72
0
4
Order By: Relevance
“…Several studies have reported that daily physical activity (PA) provides an important stimulus over musculoskeletal system that could be capable of improving muscular strength by increasing fat free mass. [16][17][18] We have previously reported that meeting current PA recommendations is associated with a better cardiorespiratory fitness in adolescents, 19 but is unknown whether it is also associated with a higher muscular strength and fat free mass.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that daily physical activity (PA) provides an important stimulus over musculoskeletal system that could be capable of improving muscular strength by increasing fat free mass. [16][17][18] We have previously reported that meeting current PA recommendations is associated with a better cardiorespiratory fitness in adolescents, 19 but is unknown whether it is also associated with a higher muscular strength and fat free mass.…”
Section: Introductionmentioning
confidence: 99%
“…In adults, both morphological and neurological adaptations explain the increase in strength (Aagaard 2003;Aagaard et al 2002). In children, recent studies demonstrate that increased general physical activity (12 months to 6 years) results in enhanced total lean body mass (Baxter-Jones et al 2008;Stenevi-Lundgren et al 2009). However, resistance training (up to 20 weeks) has not been shown to result in muscle hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“…protein synthesis; lean body mass; youth; physical activity; protein requirements PHYSICAL ACTIVITY is an essential component for the optimal growth and development of the musculoskeletal system in children. Greater levels of physical activity, especially those which are weight bearing and of higher intensity, have been associated with higher bone mineral density, lean mass, and strength in children (5,18,43). The net gain in lean mass with physical activity would require alterations in whole body protein turnover that would favor the net synthesis of body proteins, or, in other words, protein synthesis would be chronically elevated above protein breakdown.…”
mentioning
confidence: 99%